Digital tools for preventing care-related infections in intensive care units: Integrative review (Research, Society and Development, 2024)
The study aimed to map digital tools with collective interventions and potential guidelines and limitations in preventing infections related to care in intensive care units. This is an integrative review of the literature, to survey the articles in the literature, a search was carried out in the following databases: Latin American and Caribbean Literature in Health Sciences and Medical Literature Analysis and Retrieval System Online, National Library of Medicine and National Institutes of Health and Nursing Database in the period from April to May 2022. Inclusion criteria: articles published in Portuguese and English, in the years 2011 to 2021, available free of charge and in full. Articles that did not have a well-defined research design were excluded. 1,666 articles were found, after defining the inclusion and exclusion criteria, 305 articles remained, of which ten articles were included in the search. The use of applications is very common among health services and helps organize data, enabling access to information in real time and/or remotely. It is worth mentioning that the development methods of these technologies are complex, involving a mix of instructional, systematized, contextualized and user-centered design. The present study, given the literature found and the evidence presented, shows the importance of technologies in the critical environment in terms of preventing infections, as well as the relevance of constantly updating and building technologies that promote the prevention and optimization of diseases in the process of work.